Public Health Problems in Low and High Socio Economic Areas of Karachi, Pakistan - HA Qazi; J Ahmed Soomro; A Hashmi; M Hafeez Qadri; F Rasheed; M Tariq Karim (Tehran University of Medical Sciences, 2009)
Background: Despite many media campaigns by government and private sectors highlighting, water and sanitation treatment plans and policies, the public health problems are still common in different socioeconomic areas. The objective of our study was to explore the major public health problems prevailing in two different socio economic areas in Karachi, Pakistan. Methods: A cross sectional survey was conducted from January 1, 2008, to June 15, 2008. Convenience sampling was used to select the EVACUE housing situated and model village. From each house selected, interviews were conducted based on one participant per house. The main outcome variables were measure of different qualities of drinking water safety, taste, etc. Problems of waste and sanitation included disposal of solid waste and leakage of drainage system in the area. Results: The results found water quality to be good with safe drinking water and less residents complained in EVACUEE as compared to Model. The results also found better sanitary services with proper drainage system and less open dumping of garbage in EVACUEE as compared to Model. Conclusion: Health problems of drinking water and sanitation were more prevalent in low socio economic areas as compared to higher socio economic area.